Analytical and Comparative Analysis of Copper Industry Development Programs in Iran - Adel Rouhi Jouybari; Seyed Mohammad Esmaiel Jalali (Journal of Economic Geology)
Iran is considered one of the countries with a relative advantage in the field of mining and related industries due to its important mineral resources and reserves. This issue increases the importance and priority of development programs in the mining and mineral industries sector. Copper, after steel, ranks second among the major metals in terms of value-added production in the world. Iran, with a reserve of about 34 million tons of copper, owns 4% of the world's copper reserves. This article examines the analytical and comparative analysis of copper industry development programs in Iran and India. Although both countries have started their own development programs in the copper industry almost simultaneously, India was ranked among the top economic powers in Asia in 2018 compared to Iran. On the other hand, with some economic growth indicators surpassing China, some analysts believe that this trend may continue and India may achieve growth similar to China and even replace it. On this basis, India’s strategic plans in the field of copper can greatly help in formulating strategic plans in Iran’s copper industry. According to studies conducted in Iran, the most important challenges in the copper industry include increasing the amount of government salaries and export duties, non-entry of mining and industrial machinery, round-the-clock laws, and fluctuations in exchange rates and inflation. This research has examined the damage and analysis of the strengths and weaknesses of Iran’s copper industry program, reviewed the current situation and copper industry development programs, compared it with India, and addressed the challenges ahead. Finally, solutions have been proposed for the development of this important industry.